Teaching through gamification - Espinoza Freire, Enrique (2018)
The analysis of the advantages that can have the gamification of the teaching in front of the reproductive forms and mechanics of the traditional methodology is the objective of this communication; based on a bibliographical study, a construction of a diagnosis and the interpretation of those data that it allowed to arrive to conclusions on the advantage of the virtual games as long as they contribute to the elevation of the effectiveness of the teaching, because they activate the motivation, the interest and the conscious reflection. The analyzed foundations indicate the beneficial thing that it is the application of these technological resources and the prediction of the possibility of efficiency and validity of the video games in the learning of the thematic one "The Solar System" that has been evaluated starting from the faulty results of the methodology traditional employee in the teaching of this content of the subject of Social Studies.